2010
DOI: 10.1002/hyp.7921
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and processes of bank erosion at a small stream in Denmark

Abstract: Abstract:River banks are important sources of sediment and phosphorus to fluvial systems, and the erosion processes operating on the banks are complex and change over time. This study explores the magnitude of bank erosion on a cohesive streambank within a small channelized stream and studies the various types of erosion processes taking place. Repeat field surveys of erosion pin plots were carried out during a 4-year period and observations were supplemented by continuous monitoring of volumetric soil water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
(118 reference statements)
3
19
0
Order By: Relevance
“…The effects of soil type on water quality are potentially challenging to determine, first since concentrations in soil can be a combination of both human activities and natural background concentrations (Sheppard et al 2009), and second due to the complex chemical and physical structure of the soil (Pennanen 2001). The most important characteristics of soil on water quality are soil moisture, grain size and hydraulic conductivity (Veihe et al 2011). In this study, land use was not found to be an important predictor of DO, but instead the models benefitted most from the inclusion of additional watershed variables.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of soil type on water quality are potentially challenging to determine, first since concentrations in soil can be a combination of both human activities and natural background concentrations (Sheppard et al 2009), and second due to the complex chemical and physical structure of the soil (Pennanen 2001). The most important characteristics of soil on water quality are soil moisture, grain size and hydraulic conductivity (Veihe et al 2011). In this study, land use was not found to be an important predictor of DO, but instead the models benefitted most from the inclusion of additional watershed variables.…”
Section: Discussionmentioning
confidence: 99%
“…In Danish rivers, a study using erosion pin produced values ranging between 25 and 36 mm year −1 (Kronvang, Audet, Baattrup-Pedersen, Jensen, & Larsen, 2012). Similarly, in another study on a 16-km 2 Danish agricultural catchment, Veihe et al (2010) estimated a loss of material of 17.6 to 30.1 mm year −1 . The results obtained for the current bank dynamics along a small stream are, therefore, comparable to the results of previous studies performed on small agricultural catchments.…”
Section: Quantifying Bank Erosion Over One Hydrological Yearmentioning
confidence: 95%
“…The partitioning of phosphate among its various states determines its bioavailability for uptake by organisms, which is directly tied to its importance as a limiting nutrient. The relative abundance of bioavailable phosphorus in sediment has been shown to vary markedly within single study sites (1-55%; Veihe et al, 2011) and between study areas (averaging 0.5-22% of total phosphorus; Nellesen et al 2011;Thompson and McFarland 2007;Hubbard et al 2003;McDowell and Sharpley 2001;McDowell and Wilcock 2007;Howe et al 2011). …”
Section: Phosphorus Loading and Bank Erosionmentioning
confidence: 99%
“…Sensitivity analysis looks to quantitatively apportion variance in this Study Location Bledsoe et al, 2000 Mississippi, USA Hongthanat, 2010 Iowa, USA Howe et al, 2011 Vermont, USA Hubbard et al, 2003 Mississippi, USA Kerr et al, 2011Australia Merritts et al, 2010 Pennsylvania / Maryland, USA Nellesen et al, 2011 Iowa, USA Peacher, 2011 Missouri, USA Schilling et al, 2009 Iowa, USA Thompson and McFarland, 2007 Texas, USA Tufekcioglu, 2010 Iowa, USA Veihe et al, 2011 Denmark output distribution to each of the input variables. Sensitivity analysis may be local or global.…”
Section: Sensitivity Analysismentioning
confidence: 99%